ARE THERE SPECIFIC MPI STUDY VARIABLES THAT CAN DISTINCT ISCHEMIC FROM NONISCHEMIC CARDIOMYOPATHY - Vavlukis, Marija; Pop Gjorcheva, Daniela; Majstorov, Venjamin; Kostova, Nela; Peovska, I; Zdravkovska, M; Stojcevski, S (My University, 2012)
Aim of the study: To identify MPI SPECT variables distinctive for nonischemic dilated cardiomyopathy (NIDCM). Material and methods: We analyzed 47 patients with DCM who underwent MPISPECT, divided in two groups: with IDCM (27), and NIDCM (18). We analyzed clinical and MPI SPECT hemodynamic, ECG, functional response to pharmacologic stress with dipyridamol, left ventricular functional and myocardial perfusion variables.Results: No differences were found for clinical except for LBBB (table), nor for LV functional variables. Variables with differences are presented in the table.Signiﬁcant correlations with NIDCM: LBBB (r 0.446/p 0.002); patchy distribution (r 0.660/p 0.000); ST deniv. during stress (r -0.560/p 0.000); ﬁxed (r -0.540/p 0.000); reversible defect (r -0.461/p 0.001); L/H ratio (stress r -0.805/p 0.000 and rest r -0.858/p0.000). Multivariate logistic regression analysis (R square 0.700, sig = 0.000) identiﬁed ﬁve in-dependent predictors of NIDCM: patchy distribution (OR 1.97, p=0.056), ST denivelation (OR -4.34, p=0.000).
Keywords: MPI; ischaemic cardiomyopathy